Membangun Generasi Tangguh Bencana Meningkatkan Wawasan Dan Sikap Siswa SMPN 1 Songgon Kabupaten Banyuwangi - Efendi, Achmad; Balqis, Rani Diana; Anitarini, Fani; Ivan Rachmawan; Riyan Dwi Prasetyawan; Ardhi Khoirul Hakim (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
Disaster mitigation education in the school environment is becoming increasingly vital in anticipating and responding to the threat of natural disasters. This research explores the impact of disaster mitigation training at SMPN 1 Songgon, Banyuwangi, conducted with the Regional Disaster Management Agency (BPBD) Banyuwangi, focusing on the concept of “Disaster Resilient Schools”. The community service method was to bring about changes in the awareness and preparedness of the school and community towards disasters. The results of the service showed that the training has made a significant contribution in improving the understanding of disaster risks and appropriate mitigation strategies. In addition, close collaboration between the school with UKM. Resima Stikes Banyuwangi and BPBD has been established, strengthening sustainable mitigation efforts. The training also encouraged active participation of students and teachers, and built a strong support network among various stakeholders. This activity not only provided new insights into the importance of disaster mitigation education in schools, but also provided practical guidance for the development of similar programs in other school settings. The implications of this service are very important in improving disaster preparedness and resilience at the local level, as well as contributing to a better understanding of effective disaster mitigation practices. The conclusion of this service is that it is very important and necessary to implement this activity in school environments throughout Banyuwangi district.